Potensi Usaha Tanaman Sagu Dalam Mendorong Perekonomian Masyarakat Di Desa Sebagun Kecamatan Sebawi - Ananda, Iva Ashari (Sebi : Studi Ekonomi dan Bisnis Islam, 2023)
Sago has enormous potential in meeting food needs. This plant only needs to be planted once, and after 12 years it can be continuously harvested, without the need to clear land for new plantings. Sago also does not need fertilizers, pesticides and other things. The potential of the sago plant business is one of the livelihoods of the people in Sebagun village, Sebawi sub-district, with an area of ​​​​about 200 hectares. It turns out that it can provide distinct benefits for economic independence for the people in the village. The proof is that many young sago stems are found in areas that have a high enough water content, this can be a source of increasing regular or side income for the community.